Implementation of Contracts for Creative Economy Activities as Debt Guarantees - Mahaputeri Wisnuhardjo; Mohamad Fajri Mekka Putra (IHSA Institute, 2022)
With the enactment of Government Regulation Number 24 of 2022, creative economy actors can now apply for financing based on intellectual property. Intellectual property that is used as the object of debt guarantees is a fiduciary guarantee on intellectual property, contracts in creative economic activities, and collection rights in creative economic activities. Contracts in creative economic activities are objects that are still foreign to be used as collateral for debt, so it is still unclear about the implementation and how a contract in creative economic activities can become an object of debt guarantee. The research method used in this research is normative juridical. The result of this research is that contracts for creative economic activities can be used as collateral for debt by nominating the contract. Suggestions that can be conveyed based on research conducted are the need for clearer arrangements regarding the assessment and implementation of creative economic activity contracts as debt guarantees, because the elements of creative economic activity contracts and debt guarantees are quite different.